Comparative study of extraction methods for nutritional and safety assessment of fish oils from Heterotis niloticus co-products - Diana Ngo Hagbe; Fabrice Fabien Dongho Dongmo; Aymar Rodrigue Fogang Mba; Fabrice Hervé Njike Ngamga; Boris Simo Noutsa; Landry Lienou Lienou; Rebecca Madeleine Ebelle Etame; Inocent Gouado (Applied Food Research)
This research explores the quality and nutritional value of oils from Heterotis niloticus co-products (viscera and carcasses) and the impact of different extraction methods. It compares cooking-pressing, exudation, and solvent extraction (Bligh and Dyer) to identify the best technique for maximizing oil yield and preserving nutritional quality. Key parameters include chemical quality indices, fatty acid profiles, and nutritional indices. The study also assesses vitamin and mineral content, heavy metal levels, and potential health risks. Results show viscera yield the highest oil extraction rates (45.59–53.57 %). All oil samples met acceptable chemical quality standards, except for the acid value, which slightly exceeded the recommended standard. Notably, the cooking-pressing method outperformed the solvent extraction method in preserving unsaturated fatty acids. This method also resulted in lower atherogenicity (0.67) and thrombogenicity (0.59) indices, suggesting a reduced risk of cardiovascular diseases, and higher health-promoting indices. Thus, oil extracted from viscera using the cooking-pressing method is identified as a valuable source of n-3 PUFAs, particularly eicosapentaenoic (17.04 mg/g) and docosahexaenoic (45.05 mg/g) acids, which are essential for cardiovascular and overall health. However, the oil's low vitamin and mineral content suggests it should not be the primary source of these nutrients. This research supports sustainable fish processing by utilizing co-products and improving the nutritional quality of fish oils.